Uncertainty significantly influences healthcare policy decisions - Mello-Sampayo, F. de. (Man and the Economy: The journal of The Coase Society, 2025)
Uncertainty significantly influences healthcare policy decisions, especially regarding lockdown exits during pandemics. This study examines both epidemiological and economic and social uncertainties affecting stay-at-home and essential workers concerning COVID-19 exposure. Using an epidemiological real options model, we assess how these uncertainties impact the timing of lockdown exit decisions. The results indicate that a higher policy-change value lengthens the lockdown delay. A greater shock correlation between stay-at-home and mask-only populations reduces this value, leading to earlier lockdown exits. By conceptually incorporating economic and social pressures, such as income disruption, public fatigue, and policy irreversibility, the model provides a more realistic understanding of the trade-offs faced by decision-makers. These findings bridge the discrepancies between public health recommendations and policymakers’ actions. Integrating options theory enables more informed decision making by considering uncertain risks and outcomes.